(untitled) (Asian Journal of Applied Sciences, 2017)
Probiotic encapsulation approach has the potential to protect microorganisms and to deliver them into the gut. Because of the promising preclinical and clinical results, probiotics have been incorporated into a range of products. However, there are still many challenges to overcome with respect to the encapsulation process and the conditions prevailing in the gut. Thus in this study, the release activity of encapsulated L. plantarum NBRC 3070 and Aloe vera gel within alginate coated chitosan matrices during simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) exposure were investigated. There were four groups of beads prepared in this study: 1) Encapsulated probiotic and Aloe vera within alginate beads (chitosan coated), 2) Encapsulated probiotic within alginate beads (chitosan coated), 3) Encapsulated probiotic and Aloe vera within alginate beads (uncoated) and 4) Encapsulated probiotic alone within alginate beads (uncoated). Encapsulation process was carried out using extrusion method. The optimized composition of alginate matrix (1.34% w/v) and Aloe vera gel (1.99% w/v) were used.Â In order to investigate their release activity, all beads were exposed in Simulated Gastric (SGF) at pH 2.5 and Simulated Intestinal Fluids (SIF) at pH 6.5 for 120 min and 270 min, respectively. Based on the findings, alginate-Aloe vera beads with chitosan coated was able to protect L. plantarum NBRC 3070 during SGF exposure with only 1 log10 cfu/mL reduction. The presence of Aloe vera gel in the beads improved the survivability of the cells. Encapsulated cells were observed successfully slow released of cells from the beads after exposure in SIF. Scan Electron Microscope (SEM) result had shown that cross link activity of the optimum alginate-Aloe vera with chitosan coating resulted in better survival of cells after simulated gastro and able to deliver sufficient probiotic dose to intestinal region. The combinations were able to improve encapsulated cells survivability during low acidic environment passage and release activity into the intestinal target region.Â Â